2022
DOI: 10.52041/serj.v21i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Data-Driven Machine Learning With Educationally Designed Jupyter Notebooks

Abstract: This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To answer the research question, we investigate three computational essays created by students, which were already analyzed (Fleischer et al, 2022). Further evidence is drawn from recordings of the students' oral presentations of their essays and subsequent interviews regarding their experiences using worked examples and creating computational essays.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To answer the research question, we investigate three computational essays created by students, which were already analyzed (Fleischer et al, 2022). Further evidence is drawn from recordings of the students' oral presentations of their essays and subsequent interviews regarding their experiences using worked examples and creating computational essays.…”
Section: Methodsmentioning
confidence: 99%
“…A more detailed description of the data science course and the worked example is given in (Fleischer et al, 2022). The authors analyzed the same data regarding the second computational essay and found that the worked example provided good support for technically creating a competitive decision tree using machine learning.…”
Section: Context Of the Study And Previous Findings: The Prodabi Data...mentioning
confidence: 99%
See 3 more Smart Citations